Volume absorbent bandage-drainage for the treatment of gunshot wounds of soft tissues - Михайлусов, Ростислав Николаевич (ScienceRise: Medical Science, 2016)
The volume absorbent bandage-drainage was elaborated and clinically tested for the treatment of the gunshot wounds of the soft tissues. The aim of research was in elaboration of absorbent bandage-drainage for wounds with the small surface sizes (less than 30 cm) and analysis of its use for the treatment of the gunshot wounds of soft tissues. Methods. The volume absorbent bandage-drainage was use in 37 wounded with gunshot wounds of soft tissues with different localization. The control group included 42 wounded with the gunshot wounds of soft tissues who underwent the treatment by the wet-drying bandages with antiseptic solutions with further use of the gause bandage with ointment “Levomicol”. There were assessed the change of the local status of the wound, intensity of the pain syndrome on the visual analogous scale (VAS), the number of surgical processings, duration of hyperthermia, number of bandagings. Results. The use of the volume absorbent bandage-drainage in the treatment program for patients with the gunshot wounds of soft tissues allowed reliably reduce the term of the wound purification, diminish the terms of primarily-delayed suturing, diminish the term of the wound healing. Conclusions. The results of elaborated bandage-drainage indicate the effectiveness of its use at the treatment of the gunshot wounds of soft tissues with the size of surface holes less than 3,0 cm. The use of the volume absorbent bandage-drainage allows speed up the process of the gunshot wounds purification, diminish the number of complications and surgical interventions